Strategi pendidikan keaksaraan lanjutan berbasis potensi lokal - Mukhlis Mukhlis; Listyaningrum Listyaningrum; I Made Sumartana; I Gusti Bagus Rai Utama (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to (1) identify literacy programs that have been running independently in Limbung Village. (2) Determine strategies that can be carried out as additional content in the implementation of advanced literacy learning programs based on the local potential of Limbung Village. To determine the literacy strategy, the researcher uses qualitative methods in a complete, comprehensive, and holistic way. Informants in this study were determined through the snowball sampling technique, with the category of people living in Limbung Village, Sui Raya District, Kubu Raya Regency, and recorded as illiterate persons, tutors, and community leaders. Data collection techniques in this study were carried out using observation, interviews, focus group discussion techniques, Literature Studies, and Documentation. The data were analyzed qualitatively through the process of collecting, reducing, and presenting data. The results of this study are a strategy model that can improve literacy and the functioning of local communities to be more empowered and productive both economically and socially based on community needs by utilizing existing local potential is the development of advanced literacy education programs in the form of potential natural resources, human resources, institutions formal and non-formal as well as family values and cooperation. The novelty of this research is the research output that contributes to improving the functioning and empowerment of the community in the implementation of advanced literacy learning programs based on local potential.